The use of parallel computers to solve nonlinear spatial optimisation problems: an application to network planning. - Birkin, Mark; Clarke, M.; George, F. (Environment & Planning A, 1995)
The writers describe how, through considering an automaker's U.K. dealer network, they have implemented and solved a complicated problem of real-world nonlinear spatial network optimization on a parallel computer. They discuss the methods by which nonlinear spatial optimization problems may be solved and demonstrate how existing solution procedures are hindered by the computational complexity of the problem and how these obstacles can be overcome by the application of parallel computing technology. The writers conclude that they have demonstrated for the first time that parallel computers can offer real practical advances in geographical problem solving.